ADVANTAGES OF USING VIRTUAL LABORATORIES IN MEDICAL CHEMISTRY PRACTICAL CLASSES - Sevinchova Dilobar Negmatovna (Bright Mind Publishing, 2025)
The article examines the pedagogical and methodological advantages of using virtual laboratories in the teaching of Medical Chemistry. It highlights how digital simulation tools enhance students’ understanding of complex chemical processes, improve experimental accuracy, and ensure safety during laboratory training. Virtual laboratory environments enable interactive learning, allow students to repeat experiments without material limitations, and facilitate the development of analytical and problem-solving skills essential for future medical professionals. The use of virtual laboratories also contributes to increasing students’ motivation, cognitive activity, and self-directed learning. The article emphasizes that integrating virtual technologies into medical chemistry education promotes the formation of professional competencies and supports a practice-oriented learning approach.
Keywords: Medical chemistry, virtual laboratory, digital education, simulation technology, interactive learning, professional competence, cognitive activity, motivation, innovative pedagogy.